Fatores motivacionais relacionados à prática da caminhada e corrida por mulheres quilombolas da comunidade do rio itacuruçá - ARAÚJO, Maik Willem Carvalho de (2022)
The present study aimed to analyze the motivational factors related to the practice of walking and running by women from the Quilombola community of the Itacuruçá River. The sample consisted of 37 women and the Inventory of Motivation for Regular Physical Activity Practice, the IMPRAF-54, was used for data collection, which has as parameters to verify, through 54 grouped items, the six motivational dimensions (Stress control, health, sociability, competitiveness, aesthetics and pleasure) according to the Table of Norms (percentiles, deciles and coatis) validated by Barbosa and Balbinotti (2006). In the methodological question, descriptive statistics was applied through the realization of the averages of the six proposed factors and then, the transformation in percentile to conclude the study. The results show that 67% of the women practice walking and running for more than ten months, 46% with a weekly frequency of three to five times. In general, the main factors ordered by motivational influence were: Health (73%), Aesthetics (65%), Sociability (57%) and Competitiveness (56%). The factors that showed low motivation for the practice of women's activities were: Stress Control (51%) and Pleasure (44%). In conclusion, it was found that the main motivational factors related to the practice of walking and running were Health and Aesthetics. The dimensions with the lowest potential were related to Stress and Pleasure Control.